P-glycoprotein induction: an antidotal pathway for paraquat-induced lung toxicity - Dinis Oliveira, RJ (2006)
The widespread use of the nonselective contact herbicide paraquat (PQ) has been the cause of thousands of deaths from both accidental and voluntary ingestion. The main target organ for PQ toxicity is the lung. No antidote or effective treatment to decrease PQ accumulation in the lung or to disrupt its toxicity has yet been developed. The present study describes a procedure that leads to a remarkable decrease in PQ accumulation in the lung, together with an increase in its fecal excretion and a subsequent decrease in several biochemical and histopathological biomarkers of toxicity. The administration of dexamethasone (100 mg/kg ip) to Wistar rats, 2 It after PQ intoxication (25 mg/kg ip), decreased the lung PQ accumulation to about 40% of the group exposed to only PQ and led to an improvement in tissue healing in just 24 It as a result of the induction of de novo synthesis of P-glycoprotein (P-gp). The involvement of P-gp in these effects was confirmed by Western blot analysis and by the use of a competitive inhibitor of this transporter, verapamil (10 mg/kg ip), which, given I h before dexamethasone, blocked its protective effects, causing instead an increase in lung PQ concentration and an aggravation of toxicity. In conclusion, the induction of P-gp, leading to a decrease in lung levels of PQ and the consequent prevention of toxicity, seems to be a new and promising treatment for PQ poisonings that should be further clinically tested.